UPLC-Q-TOF-MS Study of the Mechanism of THSWD for Breast Cancer Treatment - Duan, Xianchun; Pan, Lingyu; Bao, Qiuyu; Peng, Daiyin (Frontiers in Pharmacology, 2020)
Taohong Siwu decoction (THSWD), a classic traditional Chinese medicine (TCM) prescription, is widely used in clinical treatment of gynecological diseases and cerebrovascular diseases. However, in this study, an ultra performance liquid Chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) method together which in both positive and negative ion mode was established to investigate the major constitutions in THSWD. A Waters ACQUITY UPLC BEH C18 column( 2.1 mm×100 mm, 1.7 μm)was used to separate the aqueous extract of THSWD. 0.1% aqueous formic acid (A) and acetonitrile (B) were used as the mobile phase. At the same time, the pathological changes of tumor and the expression of IL-4 in serum of breast cancer mice were detected after THSWD treatment. 95 components were identified in two different ion modes including aromatic acids, flavones, polysaccharides, volatile oils monoterpene glycosides,aromatic cyanogenic glycosides and others. THSWD has obvious therapeutic effects on breast cancer mice. The results establish a material basis of THSWD for the treatment of breast cancer for the late study.